ENVIRONMENTAL AND ECOSYSTEM DAMAGE - Al Faizah Imanina Yunas; Sri Marlina; Iswandi Umar; Erianjoni Erianjoni (Universitas Negeri Padang, 2020)
The environmental damage is the deterioration of the environment with the loss of water resources, air, and soil; ecosystem damage and extinction of wild fauna. The cause of environmental degradation, in general, can be categorized into two factors: the result of natural events and human-induced. Nature is very important for the survival of human life. The role provided by nature cannot be separated from the natural services themselves, which are known as ecosystem services. Damage that occurs in various ecosystems, causes the components that make up an ecosystem such as diversity of varieties, diversity of species is also disturbed. As a result of ecosystem degradation that has occurred, there is a lack of services they can provide to humans. The types of services needed and the amount of dependence of each community group on ecosystem services are different. Earth would not be able to be used as a place for life to take place if it were not for living things such as plants that have created and maintained a suitable atmosphere, decomposing organisms that have worked for our lives so that they can prevent our civilization from being buried from the waste that we produce. Keywords: Environmental Damage, Ecosystem, Ecosystem Degradation.